2013
DOI: 10.1136/bjophthalmol-2013-303452
|View full text |Cite
|
Sign up to set email alerts
|

Chemoreduction improves eye retention in patients with retinoblastoma: a report from the German Retinoblastoma Reference Centre

Abstract: In this retrospective single-centre study, chemoreduction, including cyclophosphamide, with or without focal treatment, effectively controlled retinoblastoma progression without requiring enucleation or EBRT. Addition of cyclophosphamide is safe, and allows reduction of carboplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Chemotherapy was defined as adjuvant chemotherapy, chemoreduction, thermochemotherapy, or any combination of these. The standard chemotherapy regimen in Germany for chemoreduction and neoadjuvant chemotherapy consisted of six cycles of chemotherapy resulting in cumulative doses of 1.2 g/m 2 carboplatin, 4.8 g/m 2 cyclophosphamide, 9 mg/m 2 vincristine, and 1.8 g/m 2 etoposide . Prior to the introduction of this chemotherapy regimen, different chemotherapy protocols were used.…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy was defined as adjuvant chemotherapy, chemoreduction, thermochemotherapy, or any combination of these. The standard chemotherapy regimen in Germany for chemoreduction and neoadjuvant chemotherapy consisted of six cycles of chemotherapy resulting in cumulative doses of 1.2 g/m 2 carboplatin, 4.8 g/m 2 cyclophosphamide, 9 mg/m 2 vincristine, and 1.8 g/m 2 etoposide . Prior to the introduction of this chemotherapy regimen, different chemotherapy protocols were used.…”
Section: Methodsmentioning
confidence: 99%
“…This approach involves The initial reports on IVC for retinoblastoma led the way to a new era for retinoblastoma management [5][6][7][8]. Since then, there have been numerous publications on the efficacy of IVC for retinoblastoma from around the world [28][29][30][31][32][33]. The indications for various chemotherapy protocols can vary in different retinoblastoma centers.…”
Section: Chemotherapy For Retinoblastoma: Overviewmentioning
confidence: 99%
“…Chemoreduction can effectively improve the survival rate under the premise of retaining the eyes (Aerts et al, 2013). It was reported that the cure rate reached up to 75% after 6 courses of chemotherapy (carboplatin, etoposide, vincristine and cyclophosphamide as )combined with laser, thermotherapy and other topical therapies (Künkele et al, 2013). The research of Berry et al showed that the cure rate of binoculus RB treated by chemoreduction was 47%, with the survival time of 82% of the patients was more than 12 months and 68% more than 60 months (Berry et al, 2013).…”
Section: Discussionmentioning
confidence: 99%